2008
DOI: 10.1001/archpedi.162.10.952
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of Anesthetic Agents During Peripheral Intravenous Cannulation in the Pediatric Emergency Department

Abstract: Currently, the needle-free jet injection of lidocaine device and injection of buffered lidocaine appear to provide the most cost-effective alternatives to pediatric ED physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…Multiple different modalities exist to diminish the pain associated with venipuncture in pediatric patients, with a variety of associated costs and efficacies [10]. When used appropriately; non-pharmacologic methods can be effective in dulling procedural pain.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple different modalities exist to diminish the pain associated with venipuncture in pediatric patients, with a variety of associated costs and efficacies [10]. When used appropriately; non-pharmacologic methods can be effective in dulling procedural pain.…”
Section: Introductionmentioning
confidence: 99%
“…MULTIPLE DIFFERENT MODALITIES exist to diminish the pain associated with venipuncture in pediatric patients, with a variety of associated costs and efficacies (Pershad, Steinberg, & Waters, 2008). A recent analysis indicated that the J-tip® was the most cost-effective intervention (Pershad et al, 2008).…”
Section: Background Knowledgementioning
confidence: 99%
“…A recent analysis indicated that the J-tip® was the most cost-effective intervention (Pershad et al, 2008). The J-tip® is a single-use, needle-free device which uses a pressurized carbon dioxide cartridge to force lidocaine through the skin and subcutaneously.…”
Section: Background Knowledgementioning
confidence: 99%
“…So why is the agent used with relative infrequency? The reasons are probably related to its efficacy-which is good but not 100% [158][159][160] and thus may prompt need for a coadministered agent-as well as the requirement for specialized training and equipment (for both delivery and "scrubbing" to clear this potentially teratogenic gas from the healthcare setting) [161][162][163].…”
Section: Nitrous Oxide (N 2 O)mentioning
confidence: 99%